2015
DOI: 10.1103/physrevlett.114.161801
|View full text |Cite
|
Sign up to set email alerts
|

Search for Scalar Charm Quark Pair Production inppCollisions ats=8TeVwith the ATLAS Detector

Abstract: The results of a dedicated search for pair production of scalar partners of charm quarks are reported. The search is based on an integrated luminosity of 20.3  fb^{-1} of pp collisions at sqrt[s]=8  TeV recorded with the ATLAS detector at the LHC. The search is performed using events with large missing transverse momentum and at least two jets, where the two leading jets are each tagged as originating from c quarks. Events containing isolated electrons or muons are vetoed. In an R-parity-conserving minimal sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 70 publications
4
53
0
2
Order By: Relevance
“…Predictions of FONLL have been calibrated against the accelerator data and were found to be in very good agreement, see e.g. [65,66,[73][74][75]. In particular, comparison of the FONLL simulations of the production of the B + s with the measurements at the Tevatron and at the LHC showed that FONLL predicts the low p T distribution accurately.…”
Section: Mesons At Mathuslamentioning
confidence: 94%
“…Predictions of FONLL have been calibrated against the accelerator data and were found to be in very good agreement, see e.g. [65,66,[73][74][75]. In particular, comparison of the FONLL simulations of the production of the B + s with the measurements at the Tevatron and at the LHC showed that FONLL predicts the low p T distribution accurately.…”
Section: Mesons At Mathuslamentioning
confidence: 94%
“…This stage can be inverted to populate background enriched sideband regions. These two stages, which together are referred to as the tight criteria, are used in previous ATLAS prompt-photon analyses [4][5][6][7][8][9][10][11]. In the simulation, the distributions of the shower-shape variables used for photon identification are corrected to reproduce those observed in the data.…”
Section: Event Selection and Calibrationmentioning
confidence: 99%
“…The uncertainties related to the analysis techniques are similar to those in the ATLAS inclusive photon and γ+jet analyses at 8 TeV [8,9]. Specifically, the assumption that the photon background regions are uncorrelated in the two-dimensional sideband method is assessed by varying the correlation by 10%.…”
Section: Sources Related To the Detector Calibration Include The Photmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the numerous extensions addressing the shortcomings of the Standard Model, Supersymmetry ranks among the most attractive solutions. However, if Nature is indeed supersymmetric, it is reasonable to assume that its exact realization is situated beyond the "vanilla" Minimal Supersymmetric Standard Model (MSSM) or its simplified realizations which are typically searched for in current experimental analyses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. To give an example, experimental studies typically are based on the Minimal Flavour Violation (MFV) paradigm assuming that all flavour-violating interactions stem from the Yukawa couplings alone, as it is the case in the Standard Model.…”
Section: Introductionmentioning
confidence: 99%